Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2008)
Learning curve of laser-assisted subepithelial Keratectomy: Influence on visual and refractive results Teus MA, Benito-Llopis L de, Sanchez-Pina JM, J Cataract Refract Surg 2007; 33: 1381-5. Visual performance and biocompatibility of 2 multifocal diffractive lOLs: Six-month comparative study Toto L, Falconio G, Vecchiarino L, Scorcia V, Marta Di Nicola MD, Ballone E, Mastropasqua L J Cataract Refract Surg 2007; 33: 1419-25 Central corneal thickness changes after phacoemulsification cataract surgery Salvi SM, Soong TK, Kumar BV, Hawksworth NR J Cataract Refract Surg 2007; 33:1426-1428 Pulsed electron avalanche knife: new technology for cataract surgery Priglinger SG, Palanker D, Alge CS, Kreutzer TC, Haritoglou C, Grueterich M, Kampik A Br J Ophthalmol 2007; 91: 949-54. Reproducibility and Repeatability of Central Corneal Thickness Measurement in Keratoconus Using the Rotating Scheimpflug Camera and Ultrasound Pachymetry Sanctis UD, Missolungi A, Mutani B, Richiardi L, Grignolo FM Am J Ophthalmol 2007; 144: 712-8. Diverse Clinical Presentations of Orbital Sarcoid Mavrikakis I, Rootman J Am J Ophthalmol 2007; 144: 769-75.